Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Project Based Learning (PjBL) Pada Matei Pencemaran Lingkungan Untuk Kelas X SMA: (Development of Project Based Learning (PjBL) Student Worksheets (LKPD) on Environmental Pollution Materials for Class X SMA) - Tiur Febriyanti; Nasrul Hakim (BIODIK, 2023)
The development of student worksheets (LKPD) based on Project Based Learning (PjBL) on environmental pollution material is motivated by the less varied and innovative learning media used. The media used were only in the form of PowerPoint and printed books from the library, as a result, students agreed if learning media were developed in the form of Project Based Learning (PjBL) student worksheets. This study applies the R&D (Reseach and Development) development method using the ADDIE development model steps. The results of PjBL-based LKPD product validation were declared "very feasible" by the material expert validator with a percentage of 90% and the media expert validator with a percentage of 83%. The results of the PjBL-based worksheet product trial responses that had been developed for biology subject teachers were declared "good" with a percentage of 82% and trials for students were declared "very good" with a percentage of 94.8%. This can be interpreted that the LKPD media that has been developed is very suitable to be used as an alternative learning media that can be used in the learning process in class. Furthermore, the PjBL Project Based Learning LKPD learning media on environmental pollution material can be used outside of school learning and with the implementation of Project Based Learning it is able to hone the creativity of students. Abstrak. Pengembangan Lembar Kerja Peserta Didik (LKPD) berbasis Project Based Learning (PjBL) pada materi pencemaran lingkungan dilatarbelakangi oleh media pembelajaran yang digunakan kurang bervariasi dan inovatif. Media yang digunakan hanya berupa powerpoint dan buku cetak dari perpustakaan, akibatnya, siswa setuju jika dikembangkan media pembelajaran berupa lembar kerja peserta didik berbasis Project Based Learning (PjBL). Penelitian ini menerapkan metode pengembangan R&D (Reaseach and Development) dengan menggunakan langkah-langkah model pengembangan ADDIE. Hasil validasi produk LKPD berbasis PjBL dinyatakan â€œsangat layakâ€ oleh validator ahli materi dengan persentase 90% dan validator ahli media dengan persentase 83%. Hasil respon uji coba produk LKPD berbasis PjBL yang telah dikembangkan kepada guru mata pelajaran biologiÂ  dinyatakan â€œbaikâ€ dengan persentase 82% dan uji coba kepada peserta didik dinyatakan â€œsangat baikâ€ dengan persentase 94,8%. Hal ini dapat diartikan bahwa media LKPD yang telah dikembangkan sangat layak dijadikan sebagai media pembelajaran altenatif yang mampu digunakan dalam proses pembelajaran dikelas. Selanjutnya, media pembelajaran LKPD berbasis Project Based Learning PjBL pada materi pencemaran lingkungan mampu digunakan di luar pembelajaran disekolah dan dengan diterapkanya Project Based Learning mampu mengasah kreatifitas peserta didik.